Management of Educators and Educational Staff Development in Improving the Quality of Education - Sholeh, Lukman; Sutiah, Sutiah; Arif, Makruf Al; Haq, Rosyida Rahmatul; Ummah, Kuntum Khaira; Miqdad, Miqdad (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
The focus of this research is on the management of educators and educational staff development to improve the quality of education. This research is descriptive qualitative research with a case study approach. The purpose of this research is to describe as a whole and thoroughly the management of educators and educational staff development in improving the quality of education. Data collection techniques used in this study were observation, interviews, and documentation studies. Research informants were the principal, curriculum section, teachers, and five students as respondents. Data analysis techniques using Miles and Huberman data analysis include reducing data, presenting data, and drawing conclusions. The results of this study concluded that in the management of educators and educational staff development in improving the quality of education, there are several aspects or steps: preparing programs or planning, determining needs, determining targets, determining programs, identifying learning principles, implementing programs, identifying benefits, and evaluating programs. The method used in developing educators and educational staff is on-the-job training and off-the-job training. This study implies increasing insight into managing educational institutions. The implication can develop the skills of each educator and education staff in maximizing existing programs in schools.